ANALYSIS OF MANGROVE FOREST AREA CHANGE USING LANDSAT IMAGE DATA IN ROKAN HILIR REGENCY RIAU PROVINCE - Ramadani Safitri; Musrifin Ghalib; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research has conducted in November 2016-April 2017 in Rokan Hilir Regency and was aimed to identify and inventory the data of mangrove forest area in 1994-2017 at Rokan Hilir Regency using Landsat image data analysis . The research was conducted by survey method. The quantitative method was used on the change of mangrove forest area observation. The result of 473 RGB composite on Landsat 5 and 564 RGB composite on Landsat 8 image showed the mangrove areas in 1994, 2004, 2007 and 2017 are 31,550 ha, 28,370 ha, 23,357 ha and 19,724 ha. There was a decrease of 3,180 ha in total of mangrove area in 1994-2004, in 2004-2007 was 5,013 ha and in 2007-2017 was of 3,633 ha which if added in the period of 23 years there was a decrease of 11,826 ha of mangrove area. The accuracy test of interpretation results and ground check results obtained a value of 100% accuracy, while the accuracy test between landsat images and the the results of classification obtained 95.6%.Keywords : Mangrove Forest, Change of Area, Landsat Image, Rokan Hilir